Weight Loss and Malnutrition in Patients with Parkinson's Disease: Current Knowledge and Future Prospects - Ma, Kai; Xiong, Nian; Shen, Yan; Han, Chao; Liu, Ling; Zhang, Guoxin; Wang, Luxi; Guo, Shiyi; Guo, Xingfang; Xia, Yun; Wan, Fang; Huang, Jinsha; et al. (Frontiers in Aging Neuroscience, 2018)
Parkinson’s disease (PD) is now considered a systemic disease manifested with not only motor disorders but also non-motor symptoms complexs, including psychiatric symptoms, autonomic failure, gastrointestinal problems, sensory impairment, circadian rhythm disorder. Among them, weight loss and malnutrition are commonly observed, occurring in all PD stages even several years before the diagnosis, complicating disease progression and contributing substantially to both morbidity and mortality. To date, although emerging evidence has suggested weight loss and malnutrition are associated with impaired quality of life in patients with PD, it is still unrecognized by clinicians and remains untreated. Accordingly, here, this review summarizes the evidence with respect to weight loss and malnutrition in PD, describing the weight and nutritional status, discussing its correlation with PD and related potential determinants. Given its continue progress during the course of PD, it is necessary to assess the body weight and nutritional status of PD patients routinely to early detect malnutrition as the disease progresses, and measures should be taken to restore energy balance and maintain body weight.